The Hypolipidemic Effect of Mountain Papaya and Bitter Melon Fruit Ethanolic Extract in Diabetic Rats - Heru Sasongko; Ratih Guswinda Lestari; Rika Dwi Indasari; Risky Diah Wulandari; Salistia Musta’ani (Journal of Tropical Biodiversity and Biotechnology, 2022)
Traditional medicine has been developed rapidly throughout the world to treat hyperlipidemia. However, the use of a single compound in hyperlipidemia treatment usually have low efficacy. Therefore, a combination of ingredients is bound to have  more synergistic impact in therapy. This research aimed to examine the hypolipidemic potential of mountain papaya (MPE) and bitter melon fruit ethanolic extract (BME) in alloxan-induced rats. Forty rats divided into eight groups were used in this study. Groups are divided into normal control, negative control, positive control, as well as MPE and BME groups which divided into single doses and three combination doses. Induction of 150 mg/kg alloxan intraperitoneally were performed to generate a model of diabetes and hyperlipidemia. The treatment was carried out for four weeks of the experiment. The single and combination doses of both extracts sufficiently exhibited hypolipidemic activity (p < 0.05). The levels of lipid profiles total such as cholesterol, triacylglycerides, low-density lipoprotein, high-density lipoprotein, and very high-density lipoprotein were decreased after MPE and BME administration (p < 0.05). The combination of MPE and BME also has hypolipidemic action equivalent to simvastatin. The single and combined doses of mountain papaya, as well as bitter melon fruit ethanolic extracts, have the potential to improve the biochemical (lipid profile) modifications of alloxan-induced.